(untitled) (Palíndromo, 2024)
This paper analyzes the relationship between the social tragedy of the neoliberal agenda and the political dissensus of participatory art through a specific case: the collective performance Battle of Orgreave by Jeremy Deller. Carried out in 2001, the artwork proposes the reenactment of one of the most violent conflicts of the post-war period between neoliberal policies and the working class: the tragic police attack against striking miners perpetrated during the Thatcher era in England in 1984. For the reenactment, Deller relies on the cooperation of about a thousand participants, hundreds of whom are “veterans” of the original conflict. The analysis is based on Stephanie Baker’s “social tragedy” theory, in conjunction with the concepts of “political dissensus” and “antagonism” by Jacques Rancière, Ernesto Laclau, Chantal Mouffe, and Claire Bishop. In conclusion, it is argued that the collective elaboration of a social tragedy has in the mechanics of authorial retraction one of its possible political limits.